Tingkat Kebugaran Jasmani Pemain Futsal Di Desa Bailangu Timur Kecamatan Sekayu - Suhadi Setiawan; Daryono Daryono; Agung Mahendra (Pusat Riset dan Inovasi Nasional, 2024)
The aim of conducting this research is to determine the level of physical fitness of futsal players in East Bailangu village, Sekayu subdistrict. This research method uses a deductive quantitative method with a survey research design. Using a purposive sampling technique is a sampling technique from certain data sources. Samples are taken in age categories ranging from 18-22 years. The sample used was 15 people, who were futsal players in East Bailangu village. Based on the results of this research, the results of the research and discussion showed that the level of physical fitness of futsal players in East Bailangu village, Sekayu sub-district, was mostly in the very good category, 0%, in the good category, 20%, in the fair category, 46.66%, in the poor category. amounting to 33.33% and those in the less than 0% category. The results of this research can be concluded that the physical fitness of futsal players in East Bailangu village, Sekayu subdistrict is sufficient.